2021
DOI: 10.1111/lre.12385
|View full text |Cite
|
Sign up to set email alerts
|

The role of fishery management and environmental variables on the fish fauna in floodplain lakes in the lower Purus River, Amazon Basin, Brazil

Abstract: The Amazon River basin supports the world's highest diversity of freshwater fish fauna with 2716 valid species (Dagosta & De Pinna, 2019), mainly because of the contribution and productivity of Amazon white water rivers and their associated floodplains (Crampton, 2011). Amazon floodplains are heterogeneous and dynamic environments, exhibiting seasonal water level fluctuations that strongly affect the physical structure of the habitats (Carpenter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(59 reference statements)
0
0
0
Order By: Relevance
“…Among the habitats situated in the Amazon basin, floodplains stand out as one of the most crucial ecosystems in terms of productivity and ecological heterogeneity (Crampton, 2011;Morales et al, 2019;Morales and Deus, 2021). The diversity of these floodplain areas has a great effect on the tributaries of the Amazon River, especially white-water tributaries such as the Madeira River (Fernandes et al, 2004), which presents the greatest diversity of fish species that has been catalogued for a tributary of the Amazon River (Queiroz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the habitats situated in the Amazon basin, floodplains stand out as one of the most crucial ecosystems in terms of productivity and ecological heterogeneity (Crampton, 2011;Morales et al, 2019;Morales and Deus, 2021). The diversity of these floodplain areas has a great effect on the tributaries of the Amazon River, especially white-water tributaries such as the Madeira River (Fernandes et al, 2004), which presents the greatest diversity of fish species that has been catalogued for a tributary of the Amazon River (Queiroz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Fisheries management in floodplain lakes is quite complex, since in these environments the most varied aspects have to be considered, including biological aspects and the traditional knowledge of fishers who work in these areas. However, it has been suggested that external interventions should occur on a local and reduced scale (Morales and Deus, 2021). Although the individual aspects of each lake or region must be considered, in all places it is essential to estimate the selectivity of the mostused types of fishing tackle (FAO, 1995).…”
Section: Introductionmentioning
confidence: 99%